Determination of emissions of methane and nitrous oxide in rice plantations in Guanacaste, Costa Rica - Herrera, Jorge (2013)
Methane and nitrous oxide emissions fluxes were measured in 10 rice plantations located in  Liberia, Guanacaste, working at least with 04 varieties of rice and two types of soil in the period August 2012 - April 2013. For the determination of flows static camera technique were used taking four air gas samples located in the headspace of the chamber using a plastic syringe of 12 ml at 0, 10, 20 and 30 min after camera location. The gas samples were analyzed with a gas chromatograph, equipped with FID and ECD. Averages of flow methane and nitrous oxide were recorded between 0,12 to 1,9 kg ha-1d-1 and 0,11 - 1,1 mg ha-1d-1, respectively, and no significant difference was found (p < 0,05) in the values ​​between different rice varieties and soil types subject experimental design.